Confucianism, community, capitalism : Chen Lai and the spirit of Max Weber - van Dongen, Els (SUNY Press, 2019)
Ever since Confucianism rose to the forefront of discussion among sociologists, scholars of religion, philosophers, and area specialists during the 1980s, debates on the topic have been characterized by a central tension between Confucianism as a moral project to create a fiduciary community through self-cultivation and Confucianism as a sociopolitical argument about the role of values in economic development. The tension between these two forms of Confucianism is not inherent to Confucianism. Rather, it originates in Max Weber’s critique of modernity, a critique that was influential in shaping the debate on the role of Confucianism in the modern world. Weber’s critique was at the same time concerned with the negative consequences of modernization-as-rationalization-the “iron cage of modernity”- and with the role of religious values in capitalist modernization. Whereas the former leads to the question of how to lead a meaningful life in a rational world devoid of meaning and what values could play a role in this, the latter leads to the question of the instrumental role of values in the process of rationalization. As for the latter, Weber is most famous for exploring this question in his The Protestant Ethic and the Spirit of Capitalism, in which he argued that the Protestant ethic-duty, discipline, and rational behavior-had benefited the rise of capitalism.